Electro-Oxidative Platform for Nucleophilic α-Functionalization of Ketones - Mondal, Rakesh; Jacob, Nicolas; Devuyst, Maxime; Quertenmont, Mathilde; Averochkin, Gleb; Deri, Stav; Galmidi, Lior; Gordon-Levitan, Daniel; Feller, Moran; Vantourout, Julien C.; Echeverria, Pierre-Georges; Gnaim, Samer (Synthesis, 2025)
The significance of α-functionalization of carbonyl compounds arises from its frequent use in synthetic organic chemistry. Consequently, there is a substantial and constant demand for the creation of strategies that facilitate the efficient execution of such valuable transformation. In this context, herein is presented a universal electrochemical oxidative platform for the α-derivatization of ketones with nucleophiles, employing an umpolung reactivity. This approach has been successfully employed in three distinct transformations involving C–C and C–X bond formation via straightforward nucleophilic substitution or cycloaddition reaction pathways. Furthermore, the implementation of this methodology in flow using a commercially available reactor demonstrated its inherent scalability.
Keywords: electrosynthesis; alpha-functionalization of carbonyls; umpolung; electrochemistry; flow chemistry